2006
DOI: 10.1111/j.1365-2036.2006.03093.x
|View full text |Cite
|
Sign up to set email alerts
|

The +1059G/C polymorphism in the C‐reactive protein (CRP) gene is associated with involvement of the terminal ileum and decreased serum CRP levels in patients with Crohn's disease

Abstract: SUMMARYBackground Serum C-reactive protein (CRP) levels influence the response to antitumour necrosis factor (TNF) therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…CRP, as a biomarker in this study for the evaluation of inflammatory status in ESRD patients, should be understood objectively. Although it has been widely accepted as a valuable and well recognized index of inflammation, some studies recently have reported that CRP partly depends upon commonly unmeasured factors (e. g. genetic traits) [18], [19]. In addition, as each patient had different conditions, such as age, complications, treatments, serum levels of phosphate, calcium, and intact parathyroid hormone, the data could be not well-controlled.…”
Section: Discussionmentioning
confidence: 99%
“…CRP, as a biomarker in this study for the evaluation of inflammatory status in ESRD patients, should be understood objectively. Although it has been widely accepted as a valuable and well recognized index of inflammation, some studies recently have reported that CRP partly depends upon commonly unmeasured factors (e. g. genetic traits) [18], [19]. In addition, as each patient had different conditions, such as age, complications, treatments, serum levels of phosphate, calcium, and intact parathyroid hormone, the data could be not well-controlled.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to the fact that the C-reactive protein levels peak at the beginning of the disease process and then decrease rapidly. Alternatively, this may have been due to genetic polymorphism, which has been repeatedly described in humans [33,34] the microscopic and macroscopic disease scores were very closely related to the serum calprotectin levels, which suggest that this protein reflects the state of the bowel mucosa. In medical practice, a real-time assessment of disease activity during a clinical visit has paramount importance for deciding which therapeutic strategy or diagnostic imaging technique to employ (e.g., colonoscopy).…”
Section: Discussionmentioning
confidence: 92%
“…The overlapping function may be inferred from synergistic effects on disease risk and behavior. Variants in the Wnt pathway transcription factor ( TCF-4 ) 17 and hetero- or homozygosity for the + 1059G/C polymorphism in the C-reactive protein gene 18 have also been associated with terminal ileal involvement in CD.…”
Section: Genotype-phenotype Correlations In Ibdmentioning
confidence: 99%